From stress due to E-HRM practices towards the stress due to digital communication: conceptual framework of the problematic - Khaoula, Mrs. SALMOUN; Khalid, Pr. CHAFIK (International Journal of Scientific Research and Management (IJSRM), 2019)
This research was carried out in two phases: the first, the objective of the research was to examine the sources and consequences of stress when using E-HRM. The second: after the exploratory study, the objective of the research deviated towards the analysis of the stress due to digital communication given the requirements of the studied field. In the first phase, we highlighted the effect of stress induced by E-HRM on staff satisfaction and productivity, by proposing a conceptual model that explains this relationship (conceptual model of stress induced by E - HRM), this model is based on the transactional theory of stress (Lazarus 1966) and the 2011 tarafdar model, In order to answer the following research question: How can E- HRM -induced stress affect staff satisfaction and productivity? Subsequently we tried to identify the E-HRM stressors and to ensure the feasibility of the proposed model, through an exploratory study with three “3” companies of the sector (Aeronautics and automotive). Through this study we have moved to the second phase by redirecting the theme to internal digital communication, and reformulating the problematic to be: how the stress induced by digital communication can influence the productivity Staff? The next planning step will be a continuum of the exploratory study to refine the final model, and subsequently the empirical treatment that will examine the hypotheses from the data collected. During this stage, we will start from a theory and hypotheses, towards a quantitative study which will help us to answer our problematic and to confirm or invalidate our hypotheses.